Heat transfer with nanofluids for electronic cooling. (6th January 2009) - Vasu, V.; Rama Krishna, K; Kumar, A.C.S.
In response to the ever increasing demand for smaller and lighter high performance cooling devices a new heat transfer liquids come into picture, called Nanofluids. Nanofluids are new class of heat transfer fluids developed by suspending nanosized solid particles in liquids. Larger thermal conductivity of solid particles compared to the base fluid such as water, ethylene glycol, engine oil, etc. significantly enhances its thermal properties. Numbers of phenomenological models have been proposed to explain the anomalous heat transfer enhancement in nanofluids. This paper presents systematic literature survey observed to exploit several characteristic behaviours of nanofluids viz. increase in thermal conductivity, specific heat and other thermal properties. An empirical correlation for Al2O3 + water nanofluid and effects of temperature, volume fraction and size of nanoparticle is studied. The effect of temperature on nanofluid thermal conductivity is also brought out. This behaviour combined with better mechanical properties makes fluids embedded with nanomaterials are excellent candidates for future applications.